School interaction system - Foong, Kevin Wei Pin (2014)
The operation of school system nowadays poses difficulty to users which include teachers, parents and students. For example, the used of paper to keep student attendance can pose a difficulty to the teacher to record and retrieve student's attendance. Not only that, student may easier to forget their homework when they have tones of homeworks given by different teacher from different subjects which cause the student being record in the discipline for not doing homework. Besides that, parents are unavailable during new student registration date which poses difficulty to them too. From the problems mentioned above, I have do survey to get all this information from the parents, student and school staff. In order to solve these problems, I have proposed a new paradigm of web site leveraging on web services named School Interaction System (SIS), which overcomes all these problems. In addition, it also provides both the teacher and parents with up-to-date information about their student/children in term of attendance and homework in the school. With SIS, parents able to check their student/children daily homework and attendance in school. In relation with that, student performance is increased. SIS was implemented within a centralized server whereby schools can just subscribe to the services they want. By doing this, I am also using different testing approach to test SIS in order to achieve the goals and meet the requirements. This may reduce the high maintenance cost and development cost.